Project Implementation Management of Strengthening Pancasila Student Profile (P5) Based on Local Wisdom - Ahmad Rosyid; Bayu Kurnia Kurniaaji; Meidawati Suswandari; Tri Sutrisno; Giyatmi Giyatmi (STAI Hubbulwathan Duri, 2025)
The Pancasila Student Profile Strengthening Project (P5) is one of the key initiatives of the Merdeka Belajar Curriculum aimed at improving the quality of education by fostering student character development. This study investigates the implementation of P5 at SMP Negeri 3 Sidoharjo, Wonogiri, through the lens of core management functions: planning, organizing, actuating, controlling, and evaluating. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings show that the planning stage involved meetings to define project objectives, timelines, and develop learning modules. The organizing stage included forming dedicated teams for facilitation, module development, and implementation. During the actuating phase, students were introduced to selected project themes, allowed to choose their preferred art form, design their creative outputs, engage in practice sessions, prepare the performance venue, rehearse, and finally present their work during the Panen Karya event. The controlling process was managed through activity journals maintained by teachers and direct monitoring by the vice principal of the curriculum. Evaluation consisted of diagnostic assessments at the beginning, formative assessments during implementation, and summative evaluations conducted at the final exhibition by the Facilitator Team. Overall, the findings indicate that the P5 implementation at SMP Negeri 3 Sidoharjo was carried out effectively and aligns with sound management practices, supporting the broader goals of the Merdeka Belajar Curriculum in cultivating well-rounded student character.